IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS GOOGLE CLASSROOM PADA MASA PANDEMI CORONAVIRUS DESEASE -19 DI SMK ISLAM AN NUURU TIRTOYUDO MALANG - Ahmad Firdaus; Fathurrahman Alfa; Kukuh Santoso (VICRATINA, 2021)
The application of google classroom based learning media in Islamic religious education subjects is one of the lessons applied by teachers and students at SMK Islam An Nuuru Tirtoyudo Malang. The focus of this research is on planning, implementation and several factors that influence Islamic education subjects. To achieve this goal, the researcher uses a qualitative approach based on phenomenology by using a case study type of research. Based on this research, it can be stated related to planning which can be seen from the preparation of materials, applications, and learning objectives. The implementation of this learning includes the delivery of strategies, methods, and applications that are used according to student needs and evaluation of learning. For several factors that affect the course of this learning, there are limitations of technology that can be evaluated by providing school facilities for the smooth running of this learning.